Distance Variation of Light Source Effects toward Dye Sensitized Solar Cell (DSSC) Performance using Anthocyanin Extract from Rosella Flower - Rafika Andari (JPSE (Journal of Physical Science and Engineering), 2020)
This study aims to determine the characteristics of DSSC using rosella flower extracts with variations in the distance of the light source to DSSC. The characteristics measured are current and voltage values and cell efficiency. A 150-watt halogen lamp is used as the light source. Light source was placed at a distance of 10 cm, 20 cm, and 30 cm. The voltage and current value of the halogen lamp with a distance of 10 cm to DSSC are greater than the distance of 20 cm and 30 cm. The test results show that the cell efficiency of 10 cm to DSSC is the most maximum with current (Imax) of 0.08 mA, maximum voltage (Vmax) of 306.7 mV and the efficiency of 0.046%. The smaller the distance of the halogen lamp to DSSC increases the intensity of the light so that the greater the DSSC output value. DOI: http://dx.doi.org/10.17977/um024v5i12020p031